The Relationship between Financial Development, Trade Openness and Economic Growth in Turkey: Evidence from Fourier Tests - Tatar, Havanur Ergun; Konat, Gokhan; Temiz, Mehmet (Cesky Statistical Office, 2022)
In this study, the effects of financial development and trade openness on economic growth were investigated using annual data for Turkey over the period 1960-2017. The financial development variable is represented as the ratio of financial system deposits to GDP. The trade openness variable is represented as the ratio of the sum of exports and imports of goods and services to GDP. To examine the long-run relationship between financial development, trade openness and economic growth; Fourier-based stationarity test and its complementary Fourier-based cointegration test are used. Finally, Fourier-based causality tests are also used to examine the causality relationship between the variables. As a result of cointegration tests, a long-term cointegration relationship was found between variables. According to the Fourier Toda-Yamamoto causality analysis results, it is seen that there is a one-way causality relationship from financial development to economic growth and from financial development to trade openness.
Keywords: Financial development; trade openness; economic growth; unit root; cointegration; causality; Fourier